Robotic versus total laparoscopic radical hysterectomy with pelvic lymphadenectomy for the treatment of early cervical cancer - Jagdishwar; Kiranmai; Vikas Kumar; Arun; Kaveri (Journal of Medical and Scientific Research, 2013)
Background: The aim of this study is to compare the safety, morbidity, intra operative, pathologic and postoperative outcomes of Robotic radical hysterectomy (RRH) to total laparoscopic radical hysterectomy (TLRH) in patients with early stage cervical cancer.